Stigma Negatif Perempuan Korban Kejahatan Menjadi Hambatan Dalam Pengusutan Terhadap Perbuatan Kekerasan Sebagai Bentuk Pemberian Perlindungan Hukum - Akhmad Hidayat; Alfan Afandi; Rahayu Dianasari (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2021)
Women are a group of people whose position is part of a country that is still characterized as a weak group and prone to a form of crime. Therefore, women need a form of legal protection to obtain remedies for crimes received and as a form of preventive measures to stem these crimes from recurring. The PKDRT Law, the Witness and Victims Law and the Criminal Code are regulations that can provide legal protection to women. The three laws and regulations can be a direction for law enforcers to provide a form of protection for women as victims of crime. However, in its application there are obstacles that can hinder the process of providing protection to women. This study aims to determine what obstacles can be a barrier to law enforcement officials to provide protection to women and to find out what forms of legal protection can be provided to women as victims of crime. The method in this research fosters Normative Law research which focuses on the rules and norms of positive law and data collection that has been compiled from various studies and websites that are relevant to the discussion. Based on the research results, it is found that: First, there are obstacles that occur in providing protection to women in the components of the criminal justice system. Second, that legal protection for women can be done abstractly and concretely by applying the provisions in the Witness and Victim Law, the PKDRT Law and the Criminal Code, so that the three laws and regulations can provide protection to women which is done abstractly or concretely.